Analysis of Carbon Monoxide on Transportation Along the Eastern Crossroad of Jambi - Amsori M.Das; Endi Adriansyah; Hariestya Viareco; Rifqi Sufra; Asih Suzana; Peppy Herawati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The Eastern Crossroad is one of the national roads that connect the city of Jambi with other cities, districts, and provinces, resulting in relatively heavy traffic and frequent congestion on this road. This has led to the concentration of carbon monoxide (CO), which can result in a decline in ambient air quality. The research used a quantitative descriptive approach aimed at depicting the ambient air quality of CO on Mendalo Darat Road, which is part of Eastern Crossroad. The research revealed the highest vehicle density of 17,954 units in the morning on Tuesday, with the highest emission rate of 114,290 µg/m.s, and the lowest density on Sunday morning with 6,568 units and an emission rate of 44,207 µg/m.s. The highest accumulation of CO emission levels occurred on Tuesday evening, reaching 38,536.44 µg/Nm3. Overall, the ambient air quality of CO on Mendalo Darat Road tends to exceed the quality standards. The accumulation of increased CO emissions correlates closely with the road's national status, increased vehicle density due to high community activity, changes in the day's status (working day), and road conditions with traffic signal devices.